The Contribution of Islamic Banks towards the Achievement of Sustainable Development Goals: The Case of Indonesia - Nunung Ghoniyah; Sri Hartono (Institute for Economic and Social Research, 2019)
This study aims to strengthen the opinion that the main goal of Islamic banks is not to obtain profit, but rather to improve the standards of living. In this study, the evidence is obtained by processing secondary data on Islamic banks in Indonesia during the period of 2011 to 2017 by using panel data regression model. The results of the data analysis support the hypothesis that banks whose goals are aimed at falah will demand lower payment obligations from customers, allowing the customers to manage funds in the real sector. The implication is also strengthened by good financial quality control, namely low non-performing financing value. Another form of support provided by Islamic banks, namely a more equitable cooperation contract, can also reflect Falah in every policy of Islamic banks.